2017
DOI: 10.1021/acs.macromol.7b01782
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Oriented Solid-Phase Molecular Imprinting: Toward Selective Artificial Receptors for Recognition of Nucleotides in Water

Abstract: We describe the synthesis of water-soluble molecularly imprinted polymer nanoparticles (MIP-NPs) as a new artificial host receptor for the recognition of adenosine monophosphate (AMP), used herein, as a model nucleotide. MIP-NPs were prepared by solid-phase synthesis on glass beads (GB) using, for the first time, immobilized Fe(III)chelate as an affinity ligand to orientate the AMP via its phosphate group. A polymerizable thymine monomer which can induce complementary base-pairing with the adenine moiety of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 41 publications
(23 citation statements)
references
References 44 publications
(86 reference statements)
2
20
0
Order By: Relevance
“…A high efficiency (IF, 1.57) of MIP was obtained with amide functional group at 0.2 mmol concentration and each one 0.1 mmol concentration of acid and ester functional monomers compared to high acid (IF, 1.37) or esters (IF, 1.29) functional monomer concentration (0.2 mmol). These results indicated that the amide functional monomer (N i ‐AAm) showed more specific binding capacity compared to acid (MAA) and ester (DMAEMA), and our finding is agreeable to recent study which reported that MIP nanoparticles on glass surface conjugated with Fe(II) complex prepared with N i ‐AAm functional monomer, showing high adsorption capacity for AMP nucleotide (1.35 mmol/g) . At constant concentrations of functional monomers, the effect of MBA concentration on imprinting polymer binding capacity was also studied from 0.25 to 2 mmol and among those, MIP prepared with 0.5 mmol MBA concentration showed high imprinting efficiency (IF, 1.97) compared to other concentrations.…”
Section: Resultssupporting
confidence: 90%
See 3 more Smart Citations
“…A high efficiency (IF, 1.57) of MIP was obtained with amide functional group at 0.2 mmol concentration and each one 0.1 mmol concentration of acid and ester functional monomers compared to high acid (IF, 1.37) or esters (IF, 1.29) functional monomer concentration (0.2 mmol). These results indicated that the amide functional monomer (N i ‐AAm) showed more specific binding capacity compared to acid (MAA) and ester (DMAEMA), and our finding is agreeable to recent study which reported that MIP nanoparticles on glass surface conjugated with Fe(II) complex prepared with N i ‐AAm functional monomer, showing high adsorption capacity for AMP nucleotide (1.35 mmol/g) . At constant concentrations of functional monomers, the effect of MBA concentration on imprinting polymer binding capacity was also studied from 0.25 to 2 mmol and among those, MIP prepared with 0.5 mmol MBA concentration showed high imprinting efficiency (IF, 1.97) compared to other concentrations.…”
Section: Resultssupporting
confidence: 90%
“…As shown in Supporting Information Figure S14, MIP toward ATP exhibited high binding capacity (52.7-36.8 µmol/g, IF = 1.85-2.2) compared with the non-template nucleotides and nucleosides (17.6-4.57 µmol/g) in the presence of a binary and a ternary solution. MIP exhibited high binding capacity towards ATP (52.7, 51.6 µmol/g) in the presence of Ade and ANO compared to ATP (37.8 and 39.9 µmol/g) in the presence of ADP and AMP, respectively and also in the presence of other analytes UD, UA, and Cre, which is agreeable to the previous work which reported that the ATP imprinted polymer with higher binding capacity of the ATP in single analyte solutions when compared to a ternary mixture of solutions [30]. The NIP towards ATP exhibited high binding capacity (27.6 µmol/g) in the presence of Ade and low binding capacity (16.8 µmol/g) when exposed to a ternary mixture of ADP+AMP and Ade+ANO+UD.…”
Section: Selective Binding Study Of Adenosine 5ʹ-triphosphate Imprintsupporting
confidence: 91%
See 2 more Smart Citations
“…Microorganisms (including bacteria and viruses) rely on receptor–ligand interaction to communicate with the environment . The main design obstacles of synthetic materials with microbial identification characteristics are the large target, fragile self‐assembly system and limited material properties . Surface and interface imprinting methods for proteins mentioned above have solved the difficulties of biomacromolecular imprinting .…”
Section: Biological Molecular Imprinting With Different Scalementioning
confidence: 99%